The Biosorption of Lead from Aqueous Solutions by a Wood-immobilized Fungal Biosorbent - Maini, Zomesh A N (Archīum Ateneo, 2019)
Lead [Pb(II)] biosorption capacities of immobilized Talaromyces macrosporus on Moringa oleifera L. wood were compared against pure fungal and pure M. oleifera biomass. A Pb(II) contact test of 1000 ug/mL show similar Pb(II) removal of non-immobilized fungal biomass (F) and powdered wood colonized with fungi (WP+F), with WP+F producing more biomass. Powdered sorbents had higher Pb(II) uptake compared to whole sorbents analyzed through ICP-AES, possibly due to increased surface area for Pb(II) binding. FTIR analysis of the F, WP, and WP+F identified hydroxyl, amino, carbonyl, and sulfhydryl functional groups which constitute probable Pb(II)-affinitive binding sites. The biosorbents tested in a Continuous Flow Column (CF) adsorbed Pb(II) at 1000, 2000, and 4000 ug/mL in 30 minutes with the Pb(II) uptake of WP+F producing removal efficiencies at 91-95% regardless of initial Pb(II) concentration. WP+F also showed significantly higher q values than powdered wood (WP) at 42.67184.83 mg/g for the Pb(II) test concentrations. Recovery of Pb(II) from WP+F yielded 99.61% of adsorbed ions from 1000 ug/mL Pb(II), proving Pb(II) entrapment in the sorbent. This is the first study to describe biosorption capacities for T. macrosporus and M. oleifera softwood along with the wood’s viability as an immobilization scaffold. These results show the potential of using T. macrosporus immobilized on M. oleifera wood as a tool for removal of Pb(II) in wastewater with high Pb(II) concentrations.